Differences in the Structure and Protein Expression of Femoral Nerve Branches in Rats - Shuai Wei; Shuai Wei; Shuai Wei; Qian Hu; Xiaoqing Cheng; Xiaoqing Cheng; Jianxiong Ma; Xuezhen Liang; Jiang Peng; Jiang Peng; Wenjing Xu; Xun Sun; et al. (Frontiers Media S.A., 2020)
Treatment for peripheral nerve injury remains limited. The inherent differences between motor and sensory nerve fibers in peripheral nerves should be considered to improve the effects of clinical treatment of peripheral nerve injury. In this study, we investigated the differences in protein expression and ultrastructure between the cutaneous and muscular branches of the femoral nerve in rats. Our results suggest that the cutaneous branch of the femoral nerve mainly contains sensory nerve fibers and few motor nerve fibers; Correspondingly, many motor nerve fibers and few sensory nerve fibers were observed in the muscular branch of the femoral nerve, which indicate that two branches of femoral nerve are mixed nerve. The mean thickness of the myelin sheath and basement membrane of the medullated fibers in the muscular branch of the femoral nerve was greater than that of the cutaneous branch of the femoral nerve. However, the cutaneous branch has a larger G-ratio. Gene Ontology enrichment analysis revealed that the cellular component term extracellular space was the most highly enriched, and more genes were upregulated in the muscular branch of the femoral nerve. Meanwhile, the expression of key proteins were validated by Western Blot, and immunofluorescence targets the expression of key proteins, which is consistent with the enrichment analysis of Gene Ontology. In conclusion, inherent differences in protein expression and ultrastructure were observed between the cutaneous and muscular branches of the femoral nerve in rats, which should be considered in future studies on the treatment of peripheral nerve injuries.